2015
DOI: 10.4018/978-1-4666-6547-7.ch002
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Factors Affecting Adoption of eCRM in the Australian Service Industry

Abstract: In order to grow and survive in a highly competitive market like the service industry, Electronic Customer Relationship Management (eCRM) has become a popular tool for Australian service organizations to attract, manage, and enhance customer relationships. However, due to increased competition and decreased product/services marketing cycle time, managing and building customer relationships have become a challenge for most service organizations. Ineffective eCRM adoption process can result in financial losses f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 76 publications
1
0
0
Order By: Relevance
“…Based on the obtained results, the authors conclude that the significance of factors identified as having the biggest influence is not the same with all companies, and that it differs depending on which phase of e-CRM assimilation the company is in. This is in accordance with the findings obtained for other types of IT innovations as well [6], [58].…”
Section: Comparing the Phase Of Life Cycle And The Cluster Membershipsupporting
confidence: 93%
“…Based on the obtained results, the authors conclude that the significance of factors identified as having the biggest influence is not the same with all companies, and that it differs depending on which phase of e-CRM assimilation the company is in. This is in accordance with the findings obtained for other types of IT innovations as well [6], [58].…”
Section: Comparing the Phase Of Life Cycle And The Cluster Membershipsupporting
confidence: 93%